IMPLEMENTASI FITUR TES ONLINE DI SISTEM PENERIMAAN SISWA BARU PADA SMK MUHAMMADIYAH 1 PRAMBANAN KLATEN - Eka Wahyu Sholeha; Ali Mustopa (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
Currently the development of Information Technology is increasingly possible to be able to convey information more quickly. In this article the researcher analyzes that the main problem is the length of time it takes to do the test while the limitations of the school from the committee, this causes the length of information about graduation registration, which takes approximately 1 month to determine the graduation process from the test results. Coupled with the problem of losing the registration file which is sometimes placed in any place causing the file to be lost or damaged. The process of making this system, researchers use the UML (Unified Modeling Language) design method, table design, and interface. In this study, researchers also used PIECES analysis to find out the existing problems. By using PIECES analysis so that the author can conclude several problems and produce a web "Online Test in the New Student Admission System at SMK Muhammadiyah 1 Prambanan Klaten", which is intended to help the committee solve the main problem, namely in the service of new student admissions in order to provide graduation registration information.